2017
DOI: 10.1177/1474515117745298
|View full text |Cite
|
Sign up to set email alerts
|

European cardiovascular nurses’ and allied professionals’ knowledge and practical skills regarding cardiopulmonary resuscitation

Abstract: Our study indicates a positive association between participants' performance on the practical cardiopulmonary resuscitation test and the frequency of cardiopulmonary resuscitation training and whether cardiopulmonary resuscitation training was offered in the workplace. Large ventilation volumes were the most common error at both measuring points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
1
16
2
3
Order By: Relevance
“…The percentage of correct responses for each item ranged from 29.4% to 88.2%. Compared to a study of 133 European cardiovascular nurses showing percentages of correct responses that ranged from 55% to 95% [25], the correct answer rate in this study seemed to be lower. In emergency situations such as asphyxiation and sudden death of infants, pediatric nurses should have correct knowledge to perform CPR in a precise manner and should be able to educate the parents of infants in the infant discharge education procedure.…”
Section: Chnrcontrasting
confidence: 99%
“…The percentage of correct responses for each item ranged from 29.4% to 88.2%. Compared to a study of 133 European cardiovascular nurses showing percentages of correct responses that ranged from 55% to 95% [25], the correct answer rate in this study seemed to be lower. In emergency situations such as asphyxiation and sudden death of infants, pediatric nurses should have correct knowledge to perform CPR in a precise manner and should be able to educate the parents of infants in the infant discharge education procedure.…”
Section: Chnrcontrasting
confidence: 99%
“…We also emphasised the vital importance of CPR course attendance in relation to the knowledge and performance of healthcare professionals in CPR. Pettersen et al 29 found a positive association between participants' performance on the practical cardiopulmonary resuscitation test and the frequency of cardiopulmonary resuscitation training and whether cardiopulmonary resuscitation training was offered in the workplace. Kalhori et al 25 showed a correlation between CPR course attendance and the results of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, a assistência à vítima de PCR é realizada por uma equipe multidisciplinar, esta deve ser composta por profissionais com formações diferenciadas, com habilidades especificas em atendimento emergencial. Esses profissionais devem ser guiados e orientados por um líder treinado e capacitado, disposto a coordenar o procedimento transmitindo segurança e aptidão em todo atendimento (SANTOS, 2016;PETTERSEN, 2017).…”
Section: Introductionunclassified